A Study on The Main Influencing Factors of Turnover Intention of College Teachers in Zhanjiang City, China - Jin, Minyan (Scholar: Human Sciences, 2025)
Purpose: This study examines the influencing factors of teacher turnover rate in Zhanjiang universities, China. Teacher affective commitment, burnout, continuance commitment, job dissatisfaction, and normative commitment are the independent variables, and turnover intention is the dependent variable. Research design, data, and methodology: Validity was measured using the project-objective agreement index (IOC), and Cronbach’s Alpha was used as a pilot test (n=30). The significant relationship between the variables was verified through 178 questionnaires and data statistics of Zhanjiang University teachers. This was followed by a 12-week Intervention Design Implementation (IDI) program for 30 college and university teachers. Then, the quantitative results were compared by a paired sample T-test after and before IDI. Results: According to multiple linear regression results, teacher’s affective commitment, burnout, continuance commitment, job dissatisfaction, and normative commitment have a significant impact on teachers’ turnover intention. Finally, the comparison results of the paired sample T-test show significant differences in the turnover intention of college teachers in the post-IDI and pre-IDI stages. Conclusions: According to the research results, teachers’ emotional commitment, job burnout, continuous commitment, job satisfaction, and normative commitment are important factors that affect teachers’ turnover intention.